Contrasting patterns of hot spell effects on morbidity and mortality for cardiovascular diseases in the Czech Republic, 1994-2009 - Hanzlíková, Hana; Plavcová, Eva; Kynčl, Jan; Kříž, Bohumír; Kyselý, Jan (International journal of biometeorology, 2015)
The study examines effects of hot spells on cardiovascular disease (CVD) morbidity and mortality in the population of the Czech Republic, with emphasis on differences between ischaemic heart disease (IHD) and cerebrovascular disease (CD) and between morbidity and mortality. Daily data on CVD morbidity (hospital admissions) and mortality over 1994-2009 were obtained from national hospitalization and mortality registers and standardized to account for long-term changes as well as seasonal and weekly cycles. Hot spells were defined as periods of at least two consecutive days with average daily air temperature anomalies above the 95% quantile during June to August. Relative deviations of mortality and morbidity from the baseline were evaluated. Hot spells were associated with excess mortality for all examined cardiovascular causes (CVD, IHD and CD). The increases were more pronounced for CD than IHD mortality in most population groups, mainly in males. In the younger population (0-64 years), however, significant excess mortality was observed for IHD while there was no excess mortality for CD. A short-term displacement effect was found to be much larger for mortality due to CD than IHD. Excess CVD mortality was not accompanied by increases in hospital admissions and below-expected-levels of morbidity prevailed during hot spells, particularly for IHD in the elderly. This suggests that out-of-hospital deaths represent a major part of excess CVD mortality during heat and that for in-hospital excess deaths CVD is a masked comorbid condition rather than the primary diagnosis responsible for hospitalization.
Keywords: Young Adult; Ischaemic heart disease; Cardiovascular disease; Male; morbidita; Child, Preschool; mladý dospělý; Adolescent; Mortality; Infant; Česká republika; hospitalizace; Child; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; mladiství; Central Europe; Czech Republic; novorozenec; předškolní dítě; kardiovaskulární nemoci; Morbidity; lidé; ženské pohlaví; Humans; Cerebrovascular disease; Infant, Newborn; Hospitalization; vysoká teplota; kojenec; Hot spells; Cardiovascular Diseases; Female; lidé středního věku; Hot Temperature; Middle Aged